Gestión de transporte del maracuyá y su influencia en la rentabilidad de la Cooperativa de Servicios Multiples Tanguche Chao 2018 - Pizán Gutiérrez, Janhela Yerut (2019)
The present research paper entitled "Transport Management of maracuya and its influence on the Profitability of the MULTIPLE SERVICES COOPERATIVE TANGUCHE CHAO 2018", has as general objective: to analyze the influence of transport management on the Profitability of the Multiple Services Cooperative Tanguche Chao year 2018, base don topics on logistic, transport management and profitability. The descriptive – cross-cutting design as well as the methods: inductive, analytical and dialectical were used for this research report; and the data collection techniques were surveying and documentary analysis. To this end, transport management was analysed, where the different deficiencies in the planning and control processes could be identified (representing 80% of total operating expenses); the financial statements for the years 2017-2018 were also assessed to allow the analysis of the cooperative's profitable situation, where it was observed that profitability reaches very low levels relative to its sales. Therefore, it was concluded that transport management directly influences profitability, as it was demonstrated that a 10% reduction in transport costs results in a 323% increase in operating income and of 326% in net income; which translates into an increase of 1.4% and 1.2% in operating ratios and net profitability, respectively.